Understanding the evolution of the 2014–2016 summer rainfall seasons in southern Africa: Key lessons - Emma Rosa Mary Archer; Willem Adolf Landman; Mark Alexander Tadross; Johan Malherbe; Harold Weepener; Phumzile Maluleke; Farai Maxwell Marumbwa (Climate Risk Management, 2017)
The recent 2015/16 summer rainfall season in the terrestrial Southern African Development Community (SADC) region appears to be the most severe since the droughts of the early 1980s and 1990s; with well-publicized significant impacts on agriculture and food security. Impacts have been particularly concerning since the 2015/6 season followed a poor rainy season in 2014/15, in certain areas compounding already compromised production (total maize production was, for example, down 40% relative to the previous 5 year average). This paper reviews climate forecasts and observations of the two seasons, and presents examples of the resulting impacts on agriculture within the region. We conclude by considering what may be learnt from this experience, focussing on operational recommendations for early warning within SADC, as well as longstanding needs for awareness raising and capacity building.